2003
DOI: 10.1086/368224
|View full text |Cite
|
Sign up to set email alerts
|

Local Extinction and the Evolution of Dispersal Rates: Causes and Correlations

Abstract: We present the results of individual-based simulation experiments on the evolution of dispersal rates of organisms living in metapopulations. We find conflicting results regarding the relationship between local extinction rate and evolutionarily stable (ES) dispersal rate depending on which principal mechanism causes extinction: if extinction is caused by environmental catastrophes eradicating local populations, we observe a positive correlation between extinction and ES dispersal rate; if extinction is a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 39 publications
4
86
1
1
Order By: Relevance
“…However, it remains a challenge to identify the mechanisms by which stable home ranges can emerge from unbounded movement paths, with a number of alternative modelling approaches in use [207]. In many of the existing IBMs of movement processes across complex landscapes the key questions being addressed have related to connectivity [208][209][210], emergent dispersal mortality [211,212], and home range formation [206,213,214], but in many cases these individual-based movement models have not been linked to models of population dynamics. When such links are made, it is possible to gain important new insights into the dynamics of species living on complex landscapes and into potential consequences of alternative management interventions [215].…”
Section: Process-based Modelsmentioning
confidence: 99%
“…However, it remains a challenge to identify the mechanisms by which stable home ranges can emerge from unbounded movement paths, with a number of alternative modelling approaches in use [207]. In many of the existing IBMs of movement processes across complex landscapes the key questions being addressed have related to connectivity [208][209][210], emergent dispersal mortality [211,212], and home range formation [206,213,214], but in many cases these individual-based movement models have not been linked to models of population dynamics. When such links are made, it is possible to gain important new insights into the dynamics of species living on complex landscapes and into potential consequences of alternative management interventions [215].…”
Section: Process-based Modelsmentioning
confidence: 99%
“…Simulation is terminated at the 30,000 th generation, since genetic parameters, p C, j and p K, j , are stable after 20,000 or more generations. It is difficult to interpret the absolute values of p C, j and p K, j , since individual d-values are determined by the interaction of both values with a local population density or sex ratio and relative carrying capacity, which fluctuate temporally (Poethke et al, 2003); therefore, mean d-values at 30,000th generation were used for statistical analysis. The simulation was replicated 10 times for each condition.…”
Section: Modelsmentioning
confidence: 99%
“…On the one hand, these studies have shown that the evolution of high dispersal rates may be favoured by several mechanisms such as environmental fluctuations (e.g. to cope with temporal variability of resource availability [18][19][20]), local extinction probability [20] as well as individual and kin competition [9,17,[21][22][23]. On the other hand, the fitness benefits of dispersing can be reduced by the associated risks such as dispersal costs and mortality [24], thereby promoting the evolution of lower dispersal rates [15,25].…”
Section: Introductionmentioning
confidence: 99%